Examining the Relationship Between Resilience and Perceived Stress - Kumari, Micky; Sinha, A.R. (Journal of Neonatal Surgery, 2025)
This study examines the relationship between resilience and perceived stress among undergraduate students. Stress, a common aspect of modern life, can have severe psychological consequences if not managed effectively. Perceived stress refers to an individual's subjective evaluation of stress, whereas resilience represents the ability to recover from adversity. Using the Connor-Davidson Resilience Scale and the Perceived Stress Scale, data were collected from 400 students. Pearson’s correlation analysis revealed a significant negative relationship between overall resilience and perceived stress (r = -0.243, p<.001), with personal competence, control, and spirituality contributing most to stress reduction. However, positive acceptance of change did not significantly correlate with perceived stress. These findings highlight resilience as a crucial protective factor against stress, emphasizing the need for interventions to enhance resilience and promote well-being among students.